THE IMPACT OF EFL TEACHERS' CREATIVE SELF-EFFICACY AND SELF-ESTEEM ON CREATIVE TEACHING - Rachmadhani, Nabilah; Jufrizal, Jufrizal (University of Kuningan, 2024)
ABSTRACT. Investigating the contribution of teachers' creative self-efficacy and self-esteem is crucial for enhancing creative teaching practices, particularly within the framework of Indonesia's Merdeka curriculum, which emphasizes the development of students' creativity and innovative skills. This research aimed to find out how is the contribution of teachers’ self –efficacy and self –esteem to creative teaching by using multiple regression analysis techniques. The participants of this research were six EFL teachers from senior high school Lengayang. Questionnaires and observation checklist were the instruments in this research. The results show that creative self-efficacy positively and significantly contributes to creative teaching, indicating that higher creative self-efficacy leads to better creative teaching practices. On the other hand, teachers' self-esteem contributes negatively creative teaching, suggesting that excessively high self-esteem may hinder creativity in teaching. Meanwhile, creative self-efficacy and self-esteem simultaneously contributes 81.2 percent towards creative teaching. Fostering these creative behaviors can create an engaging and supportive learning environment, enhancing student outcomes. Social support from principals and colleagues, along with a positive school climate, is crucial in boosting teachers' self-esteem and creative self-efficacy, thereby improving the quality of teaching and learning.